Melody D. Knowles, Esther Menn, John Pawlikowski, and Timothy J. Sandoval, eds. Contesting Texts: Jews and Christians in Conversation about the Bible - Boys, Mary C. (Studies in Christian-Jewish Relations, 2011)
No abstract is available.